PERAN HUKUM DALAM MENJAMIN KEBEBASAN PERS: TINJAUAN TERHADAP UU ITE DAN ANCAMAN BAGI DEMOKRASI DI INDONESIA - Aisyah, Siti; Muflihah, Iim; Khoirunnisa, Anin Nur; Septian, Farid (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Freedom of the press is an important pillar in a democratic country, which makes it easier for the public to obtain accurate and relevant information, as well as to control government performance. However, in Indonesia press freedom has quite complicated challenges due to the emergence of the ITE Law (Information and Electronics Law). Therefore, this research aims to examine the role of law on press freedom, especially looking at the ITE Law and its impact on the democratic system in Indonesia. The method used in this research is literature study or library research using books, articles, journals and other related literature. The results of this research show that articles in the ITE Law, such as defamation and the spread of news whose truth is unclear (hoaxes), are often used to blame or harm journalists and media who are vocal about the performance of the government or certain groups. This causes a feeling of fear (chilling effect) which inhibits journalism and freedom of expression. Furthermore, this research examines that the use of the ITE Law will suppress press freedom which can cause loss of access to important information for society and political participation. This research suggests that there is a need for improvements in the ITE Law to clarify the limits on press freedom, as well as increase protection for journalists and media who carry out their duties according to the journalistic code of ethics